Politik Identitas Yang Berkelanjutan: Reorientasi Etika Kebangsaan Di Era Krisis Global - Imam Mawardi; Anik Sunariyah (Penerbit STKIP PGRI Bangkalan, 2025)
Among globalization, social divisions, and the rise of symbolic politics, the dynamics of identity politics in modern democracies reveal increasingly complex symptoms of a crisis in national ethics. Identity politics in Indonesia not only offers recognition and acknowledgment to marginalized groups, but is also often used exclusively and instrumentally, causing polarization, identity conflicts, and rejection of the national values of Pancasila. The purpose of this paper is to examine how sustainable identity politics can be developed through a reorientation of national ethics in an era of global crisis. In this study, a qualitative approach was used, and critical literature review methods were employed to examine a number of academic literature discussing topics such as identity politics, democracy, social ethics, Axel Honneth's theory of recognition, Max Weber's ethics of responsibility, and thought. The analysis process was carried out through steps such as literature classification, critical-conceptual reading, and normative synthesis. The purpose of this analysis is to produce a framework of identity politics based on the principles of recognition, social responsibility, and national solidarity. The study shows that sustainable identity politics cannot be built on symbolic domination, conflict, or the exclusive affirmation of identity. Instead, it requires a foundation of inclusive ethics of recognition and dialogical social responsibility. In this situation, Pancasila is considered not only a national ideology but also a national ethic capable of balancing personal and group interests to maintain Indonesian democracy amid global threats